Relation of exhaled nitric oxide levels to development of bronchopulmonary dysplasia. Issue 3 (21st April 2009) - May, C; Williams, O; Milner, A D; Peacock, J; Rafferty, G F; Hannam, S; Greenough, A
Abstract : Objective: To test the hypothesis that exhaled nitric oxide levels on day 28 and changes in exhaled nitric oxide levels in the neonatal period would differ according to whether infants developed bronchopulmonary dysplasia (BPD) and its severity. Design: Prospective observational study. Setting: Tertiary neonatal intensive care unit. Patients: 80 infants (median gestational age 28, range 24–32 weeks), 46 of whom developed BPD. Interventions: Exhaled nitric oxide measurements were attempted on days 3, 5, 7, 14, 21 and 28. Main outcome measures: BPD (oxygen dependency at 28 days), mild BPD (oxygen dependent at 28 days, but not 36 weeks postmenstrual age (PMA)); moderate BPD (oxygen dependent at 36 weeks PMA) and severe BPD (respiratory support dependent at 36 weeks PMA). Results: On day 28, exhaled nitric oxide levels were higher in infants with BPD compared to those without BPD (p<0.001) and there was a linear trend in exhaled nitric oxide results as BPD severity increased (p = 0.006). No significances in the change in exhaled nitric oxide levels over the neonatal period were found between the four groups. Conclusion: Exhaled nitric oxide levels are raised in infants with established BPD, particularly in those developing moderate or severe BPD, and may reflect ongoing inflammation.